Pengaruh Metode Pengelasan TIG dan SMAW Terhadap Sifat Mekanik Baja Karbon SS400 (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2022)
Welding methods that greatly affect welding, heat input in a process that can affect the cooling rate, an increase in the amount of heat input used, the cooling rate will be slower, and vice versa increasing the heat input used, the cooling rate will be faster, the cooling rate is faster. will quickly increase the hardness value of the welding results. This research was conducted on 6 pieces of SS400 carbon steel plate with dimensions of 250x100x10mm. The welding method used is the TIG and SMAW method, with a welding position of 1G and the type of connection is single v butt joint, the electrode used is E6010 with a diameter of 2.6 mm. There are 3 welding samples, where sample 1 was welded by the TIG method, sample 2 by the SMAW method. and sample 3 using the combined TIG&SMAW method. Rockwell hardness testing uses the ASTM E-18 standard with area testing on weld metal, HAZ and Base metal. Tensile testing using the AWS D1.1 standard and the microstructure standard used ASTM E3. The highest average tensile strength value is found in the combined combined sample (sample 3) of 467.5 MPa. From the test results, it was found that the sample that had the highest hardness value was a combined sample of TIG and SMAW in the weld metal area of ​​34.5 HRC. The distribution of the perlitee phase in sample 1 was 15.39%. In sample 2 as much as 15.80%, and in sample 3 as much as 15.52%. The teaching method greatly affects the mechanical properties of the welding results.